VD_FINDINFO Jug / 2019 / 308 vom 14. Dezember 2020 - VD Tribunal cantonal (2020)
LÉGITIMATION ACTIVE ET PASSIVE, CONCESSION, TRUST | 16 al. 1 let. a CL, 16 ch. 4 CL, 17 CL, 18 CL, 398 CO, 84 CO, 117 LDIP, 16 LDIP, 2 CLHT